A note on Valeriana jatamansi Jones (Caprifoliaceae s.l.) - Mabberley, D.J.; Noltie, H.J. (Blumea, 2014)
The tangled arguments around the names of jatamansi drug plants are examined and the correct synonymies and typifications for Nardostachys jatamansi (D.Don) DC. and V. jatamansi Jones (both Caprifoliaceae s.l.) are provided. The conservation status of the former, and the need for further work on the subject, is briefly discussed.